2017
DOI: 10.3390/ijgi6090278
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation Skill Improvement with Geospatial Applications: Report of a Multi-Year Study

Abstract: There are several competences and spatial skills to be acquired by the student related to the treatment of geo-information in Science, Technology, Engineering, and Mathematics (STEM) disciplines. Spatial orientation is the spatial skill related to the use of georeferenced information, and geospatial applications (on-line map interfaces) such as the spatial data infrastructure offer a great opportunity for development of this skill. In this report we present several experiments, carried out over five academic y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Thus, teaching experiences carried out with engineering students revealed that an improvement of both the acquired knowledge and spatial visualization skill are achieved by using a VT. This is in agreement with previous studies [15][16][17][18][19][20] where it was demonstrated that the visualization skill can be improved through appropriate training. Taking all the previously mentioned into account, two facts can be stated: (i) the graphical design of any Didactic Virtual Tool (DVT) is a key factor in achieving an educative aim; and (ii) in the case that such a tool is used for solving any spatial visualization problem, the tool design becomes an even more influential factor.…”
Section: Introductionsupporting
confidence: 93%
“…Thus, teaching experiences carried out with engineering students revealed that an improvement of both the acquired knowledge and spatial visualization skill are achieved by using a VT. This is in agreement with previous studies [15][16][17][18][19][20] where it was demonstrated that the visualization skill can be improved through appropriate training. Taking all the previously mentioned into account, two facts can be stated: (i) the graphical design of any Didactic Virtual Tool (DVT) is a key factor in achieving an educative aim; and (ii) in the case that such a tool is used for solving any spatial visualization problem, the tool design becomes an even more influential factor.…”
Section: Introductionsupporting
confidence: 93%
“…One kind of large-scale spatial skill that has been commonly examined in studies of STEM teaching and learning is spatial orientation or perspective-taking (e.g., Carbonell Carrera & Saorín Pérez, 2011;Carbonell-Carrera & Hess-Medler, 2017;Kozhevnikov, Hegarty, & Mayer, 2002;Lowrie & Logan, 2018;Tartre, 1990). Perspective-taking is critically important for many STEM domains, such as the earth and space sciences (Hegarty, Crookes, Dara-Abrams, & Shipley, 2010).…”
Section: A Brief History Of the Research On Spatial Thinking In Psychmentioning
confidence: 99%
“…One kind of large-scale spatial skill that has been commonly examined in studies of STEM teaching and learning is spatial orientation or perspective-taking (e.g., Carbonell Carrera USING A DISCIPLINE-FOCUSED LENS TO EXAMINE SPATIAL THINKING SKILLS 8 et al., 2011;Carbonell-Carrera & Medler, 2017;Kozhevnikov, Hegarty, & Mayer, 2002;Lowrie & Logan, 2018;Tartre, 1990). Perspective-taking is critically important for many STEM domains, such as the earth and space sciences (Hegarty, Crookes, Dara-Abrams, & Shipley, 2010).…”
Section: A Brief History Of the Research On Spatial Thinking In Psychmentioning
confidence: 99%